Unlocking Potential: Managerial Development for Tourism Officers in Kampung Jenggalu Kito - Slamet Widodo; Meiliani; Rhienta Aprisella (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Kampung Jenggalu Kito in Bengkulu City possesses significant potential as a local tourist destination that can enhance the local economy. However, this potential has not been fully realized due to the limited managerial capacity of the tourism managers. Therefore, this community service program aims to improve the managerial capacity of the tourism managers in Kampung Jenggalu Kito through a series of training sessions and mentoring. The activities are designed to provide the necessary knowledge and skills related to management for the tourism managers. Through intensive training and ongoing support, it is expected that the tourism managers will develop their abilities to design and implement effective strategies, identify and address field issues, and organize resources more efficiently. The anticipated outcome of this program is an increase in the managerial competence of the tourism managers, which in turn will enhance the competitiveness and attractiveness of Kampung Jenggalu Kito as a tourist destination. Thus, this program aims not only to improve the quality of tourism management but also to promote local economic growth and the well-being of the community